Lower Limb Muscle Fatigue Alters Spatiotemporal Gait Parameters and Turning Difficulty Characteristics in Parkinson’s Disease - Halimatul Abd Ghani; Alia A. Alghwiri; Hafifi Hisham; Haidzir Manaf (Annals of Rehabilitation Medicine, 2023)
Objective To determine the effects of lower limb muscle fatigue on spatiotemporal gait parameters and turning difficulty characteristics during the extended Timed Up and Go (extended TUG) test in individuals with different severity stages of Parkinson’s disease (PD). Methods Forty individuals with PD, classified as Hoehn and Yahr (H&Y) stages 2 and 3 participated in this pre- and post-experimental study design. The participants performed a continuous sit-to-stand task from a chair based on 30 cycles/min set-up to induce lower limb muscle fatigue. They performed extended TUG test immediately before and after completing the fatigue protocol. Spatiotemporal gait parameters and turning difficulty characteristics were recorded using two GoPro® Hero 4 Silver cameras. Data were subjected to a repeated-measure ANOVA. Results Individuals with PD experience significant changes in spatiotemporal gait parameters, specifically stride velocity and length, under conditions of lower limb muscle fatigue (p=0.001). These changes were more pronounced in individuals with PD in the H&Y stage 3 group. Additionally, both PD groups exhibited difficulty with turning, requiring more than five steps to complete a 180° turn and taking more than 3 seconds to accomplish it. Conclusion These findings highlight the impact of muscle fatigue on gait performance in PD and suggest that individuals in later stages of the disease may be particularly affected. Further research is needed to explore interventions that can mitigate these gait impairments and improve mobility in individuals with PD.